2020
DOI: 10.21203/rs.3.rs-50602/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey Among Italian Pregnant Women and New-mothers During the COVID-19 Pandemic Lockdown.

Abstract: In response to the COVID-19 pandemics, drastic measures for social distancing have been introduced also in Italy. The purpose of this study was to describe some aspects of lifestyle, access to health services, and mental wellness of Italian pregnant women and new-mothers during the lockdown. We carried out a web-based survey to assess how pregnant women and new-mothers were coping with the lockdown. Expected outcomes were categorized in different analysis domains: psychological well-being and support, physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Our results were similar to two studies, one from the United Kingdom [8] and the other from Italy [13], which showed that the Covid-19 lockdown led to distress for parents who reported social isolation as a key challenge. The United Kingdom study also reported that lockdown led to shorter hospital stays, changes to the delivery plans, a lack of breastfeeding support, challenges accessing healthcare, limited social support and mental health difficulties [8], findings corroborated by our study.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were similar to two studies, one from the United Kingdom [8] and the other from Italy [13], which showed that the Covid-19 lockdown led to distress for parents who reported social isolation as a key challenge. The United Kingdom study also reported that lockdown led to shorter hospital stays, changes to the delivery plans, a lack of breastfeeding support, challenges accessing healthcare, limited social support and mental health difficulties [8], findings corroborated by our study.…”
Section: Discussionsupporting
confidence: 90%
“…Pregnant women may be particularly vulnerable to the negative psychological effects of COVD-19 public health measures (Caparros-Gonzalez & Alderdice, 2020), both because they represent the demographic most affected and because pregnancy itself entails significant life changes that require major psychosocial and emotional adjustments (Dunkel Schetter, 2011). Early reports from the current cohort (Lebel, MacKinnon, Bagshawe, Tomfohr-Madsen, & Giesbrecht, 2020) and other cohorts around the world (Ceulemans, Hompes, & Foulon, 2020;Davenport, Meyer, Meah, Strynadka, & Khurana, 2020;Durankus & Aksu, 2020;Patabendige, Gamage, Weerasinghe, & Jayawardane, 2020;Stampini et al, 2020;Taubman-Ben-Ari, Chasson, Abu Sharkia, & Weiss, 2020;Wu et al, 2020) show that symptoms of depression and anxiety have increased dramatically among pregnant individuals during the COVID-19 pandemic, with greater social isolation and disease fears appearing to predict greater risk of elevated symptoms.…”
Section: There Is a Need To Understand The Effects Of Pandemics On Mental Healthmentioning
confidence: 99%
“…Pregnant individuals may be particularly vulnerable to the negative psychological effects of public health measures related to COVID-19 [17], both because they represent the demographic most affected by disasters and because pregnancy itself entails significant life changes that require major psychosocial and emotional adjustments [18]. An early report from the current cohort [19] and other cohorts around the world [20][21][22][23][24][25][26] show that symptoms of depression and anxiety have increased dramatically among pregnant individuals during the COVID-19 pandemic, with greater fears surrounding social isolation and disease appearing to predict a greater risk of elevated symptoms.…”
Section: A Need To Understand the Effects Of Pandemics On Mental Healthmentioning
confidence: 99%